A competence development framework for learning and teaching system dynamics. (25th August 2016) - Schaffernicht, Martin F. G.; Groesser, Stefan N.
Abstract: Current teaching and learning of system dynamics are based on materials derived from the expertise of masters . However, there is little explicit reference to neither the stages which beginners go through to become proficient nor what is learned at each of these stages. We argue that this hinders cumulative research and development in teaching and learning strategies. We engaged 15 acknowledged masters in the field to take part in a three‐round Delphi study to develop an operational representation of the competence development stages and what is learned at each stage. The resulting system dynamics competence framework consists of a qualified, expert‐evaluated, empirically based set of seven skills and 265 learning outcomes. The skills provide a common orientation, in the language of current educational research, to facilitate research, course design and certification efforts to ensure quality standards. To conclude, this paper provides avenues for future work. Copyright © 2016 The Authors System Dynamics Review published by John Wiley & Sons Ltd on behalf of System Dynamics Society